Tazkiyah al-Nafs sebagai Metode Peningkatan Kesehatan Mental Peserta Didik di Era Digital - Siti Mutholingah; M. Rodhi Zamzami; Naila Nahdiyah (IAI Miftahul Ulum Pamekasan, 2025)
This study aims to analyze how the practice of improving students' mental health through tazkiyah al-nafs in the digital era and to analyze the implications of tazkiyah al-nafs as a method of improving students' mental health in the digital era. This research method uses library research type. The results of this study showed the practice of improving students' mental health in the digital era through tazkiyah al-nafs, namely through the process of muhasabah (introspection), mujahadah (self-struggle), and riyadhah (spiritual training) which are integrated and sustainable in the practice of life in the digital era. The implications of the tazkiyah al-nafs method in improving students' mental health holistically include cognitive, affective and psychomotor aspects. This study produces new findings in the form of a holistic-integrative-sustainable tazkiyah al-nafsmodel that theoretically strengthens the concept of tazkiyah al-nafs as a method of purifying the soul in the world of Sufism but can be actualized in the educational process in this digital era. Practically, this research offers an implementable framework for school counselors.